Análise da degradação da matriz extracelular (MEC) pulmonar na urina de pacientes com Doença Pulmonar Obstrutiva Crônica (DPOC) - Marinho, Regina Helena (2009)
Objectives: To analyze the levels of degradation of extracellular matrix (ECM) in the urine in patients with COPD and their correlation with pulmonary function. Methods: patients with COPD (n = 20) and healthy controls (n = 10) were selected and submitted the pulmonary function testing by spirometry. The degradation of ECM was assessed in urine samples in the group with COPD and control of two strategies: determination of hydroxyproline, to evaluate collagen degradation, and detection and determination of the concentration of elastin fragments by ELISA using anti-elastin. Results: The difference between the concentration levels of hydroxyproline in urine of patients with COPD was not different compared to the control group. However, it was observed that the concentration of elastin fragments in the urine of patients with COPD was highly significant (p=0.002) and correlated negatively with FEV1 parameter of pulmonary function tests. Conclusion: This results open perspectives for the characterization of degradation products of ECM by mass spectrometry (MALDI-TOF/LC-MS/MS), a technology highly specific and sensitive for the determination of amino acid sequences of peptides of interest.